Lipid-Polymeric Films: Composition, Production and Applications in Wound Healing and Skin Repair - Eliana B. Souto; Cristiana M. P. Yoshida; Gislaine R. Leonardi; Amanda Cano; Elena Sanchez-Lopez; Aleksandra Zielinska; César Viseras; Patricia Severino; Classius F. da Silva; Raquel de M. Barbosa (MDPI AG, 2021)
The use of lipids in the composition of polymeric-based films for topical administration of bioactive ingredients is a recent research topic; while few products are commercially available, films containing lipids represent a strategic area for the development of new products. Some lipids are usually used in polymeric-based film formulations due to their plasticizing action, with a view to improving the mechanical properties of these films. On the other hand, many lipids have healing, antimicrobial, anti-inflammatory, anti-aging properties, among others, that make them even more interesting for application in the medical-pharmaceutical field. This manuscript discusses the production methods of these films both on a laboratory and at industrial scales, the properties of the developed biopolymers, and their advantages for the development of dermatologic and cosmetic products.